Effect of Dadih Probiotics on Malondialdehyde Levels in Diabetic Mellitus Rats With Alloxan Induction - Indah Fitriani; Efrida Efrida (Faculty of Medicine, Universitas Andalas, 2023)
Objective : This research aims to analyze the effect of dadih probiotics on MDA levels in alloxan-induced diabetic rats. Methods : This study used an experimental design with a post-test-only control group. Wistar strain white rat samples were divided into 4 groups. The negative group was not given any treatment, K(+), P1, and P2 were induced by alloxan 150 mg/kg BW on the first day. Groups P1 and P2 were given dadih probiotic doses of 1.87 g/200 gBW and 3.74 g/200 gBW on days 4 to 17. Results : Measurement of MDA levels was carried out on the 18th day. Data were analyzed with One Way Anova and a post-hoc test. The research results are statistically significant if p-value <0.05. The average levels of MDA K- 2.29 nmol/mL, K+ 3.77 nmol/mL, P1 2.97 nmol/mL, and P2 2.53 nmol/mL. Based on statistical tests, there was an effect of dadih probiotics on MDA levels as evidenced by a p-value < 0,05. Conclusion : Dadih probiotic doses of 1.87 g/200gBW and 3.74 g/200gBW can reduce MDA levels in rats.